Study on the Marketing and Product Strategies of the Financial Institutions: Adapting Marketing Strategies for a Changing Financial Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Financial-banking marketing will have to undergo significant changes. The experts in this fieldwill have to abandon their traditional and opaque aggressive tactics. They will stand in front of customerswith uncomplicated merchandise dressed in bright colours. The key to relaunching lending on a healthymarket will be to change marketing tactics within a visionary, unitary strategy. The banking system willhave to keep up with Europe, not only in terms of client services, but also in terms of marketing andpromotion strategies for the banking segment, which has been in constant flux over the last decade.Social marketing will have to leave the theoretical realm at all times, and all adopted strategies will haveto pass through social responsibility precise development goals with measurable results over time